Has building innovative provinces reduce environmental pollution?--evidence from a quasi-natural experiment in China - Tang, Lu; Tang, Mengcong; Xi, Wenjia (Frontiers in Environmental Science, 2023)
The implementation of innovative provinces as a pivotal pilot measure to promote the in-depth advancement of ecology in China is a critical undertaking. An accurate assessment of the environmental effects of these innovative provinces is necessary to obtain a comprehensive understanding of the impact of pilot policies and facilitate the promotion of future policies with precision. In this study, the difference-in-differences method and the mediation model are employed to analyze the effect and mechanism of the pilot policies for innovative provinces on regional environmental pollution in 30 provinces in China from 2008-2020. The results demonstrate that the implementation of the innovative provinces pilot policy can significantly decrease environmental pollution as confirmed by the DID model, which remains valid even after conducting robustness tests. Furthermore, the intermediation effect model provides evidence that the innovation provinces pilot policy reduces environmental pollution through technological innovation and industrial structure upgrading. Additionally, the effect of the innovative provinces pilot policies on regional environmental pollution is more significant in coastal areas than in inland areas. Overall, this study contributes to the existing literature by underscoring the importance of innovation-driven development for environmental governance and effectively promoting the construction of a resource-saving and environment-friendly society.